Induction of axial chirality in divanillin by interaction with bovine serum albumin - Venturini, Diego [UNESP]; De Souza, Aguinaldo Robinson [UNESP]; Caracelli, Ignez; Morgon, Nelson Henrique; Da Silva-Filho, Luiz Carlos [UNESP]; Ximenes, Valdecir Farias [UNESP] (Public Library of Science (PLoS), 2017)
Vanillin is a plant secondary metabolite and has numerous beneficial health applications. Divanillin is the homodimer of vanillin and used as a taste enhancer compound and also a promissory anticancer drug. Here, divanillin was synthesized and studied in the context of its interaction with bovine serum albumin (BSA). We found that divanillin acquires axial chirality when complexed with BSA. This chiroptical property was demonstrated by a strong induced circular dichroism (ICD) signal. In agreement with this finding, the association constant between BSA and divanillin (3.3 × 105 mol-1L) was higher compared to its precursor vanillin (7.3 × 104 mol-1L). The ICD signal was used for evaluation of the association constant, demonstration of the reversibility of the interaction and determination of the binding site, revealing that divanillin has preference for Sudlow's site I in BSA. This property was confirmed by displacement of the fluorescent markers warfarin (site I) and dansyl-L-proline (site II). Molecular docking simulation confirmed the higher affinity of divanillin to site I. The highest scored conformation obtained by docking (dihedral angle 242°) was used for calculation of the circular dichroism spectrum of divanillin using Time-Dependent Density Functional Theory (TDDFT). The theoretical spectrum showed good similarity with the experimental ICD. In summary, we have demonstrated that by interacting with the chiral cavities in BSA, divanillin became a atropos biphenyl, i.e., the free rotation around the single bound that links the aromatic rings was impeded. This phenomenon can be explained considering the interactions of divanillin with amino acid residues in the binding site of the protein. This chiroptical property can be very useful for studying the effects of divanillin in biological systems. Considering the potential pharmacological application of divanillin, these findings will be helpful for researchers interested in the pharmacological properties of this compound.